Interpretation of Āyāt al-Aḥkām for Muslim Minorities: A Case Study of Pork Trading by Muslims in Wamena City - Rifki Rifaat; Ziyadul Haq; Syamsul Ariyadi (Jurnal Budi Pekerti Agama Islam, 2026)
Pigs hold significant economic, social, and religious value in the Wamena community, becoming an integral part of their customary law. However, the Muslim minority in Wamena faces unique challenges, as they struggle to balance local traditions with Islamic law. This study aims to explore the interpretation of Ahkām verses among minority Muslims in Wamena and analyze the Islamic laws regarding the sale and purchase of pigs in this context. The research is qualitative, combining observations and literature studies. It examines the issues surrounding pig transactions in Wamena and reviews relevant Ahkām verses along with scholarly opinions. The study identifies four patterns in the religious understanding of Wamena Muslims: traditional religion, formal religion, rational religion, and a precursor method that combines traditional practices with reasoning and revelation. Tafsir Ahkām offers solutions for minority Muslims by considering the systematic approach to Ahkām verses, hadith, and the school of jurisprudence. Despite the prohibition of pigs in the Qur’an and hadith, Wamena Muslims’ engagement in pig transactions can be analyzed using fiqh aqalliyyāt principles, such as ijtihād tarjīhi and ijtihād ibdā’i, with an emphasis on gradual implementation and accommodating Islamic and customary laws for minority Muslims in Wamena.